Does the two-chair dialogue intervention facilitate processing of emotions more efficiently than basic Rogerian conditions?. Issue 3 (3rd July 2018) - Stiegler, Jan Reidar; Molde, Helge; Schanche, Elisabeth
ABSTRACT: Processing difficult emotions is assumed to be of importance in therapeutic change. In this study, we examine whether a two-chair dialogue in Emotion-focused Therapy (EFT) is associated with a change in emotional processing, measured as changes in emotional arousal and emotional experiencing. In a multiple baseline design, 20 clients in treatment for depression or anxiety first received five, seven or nine weekly sessions of baseline treatment providing Rogerian conditions and affect attunement. In the second phase, two-chair intervention was added for the five consecutive sessions. All sessions were subdivided into 2 min segments which were rated using the Client Emotional Arousal Scale III and the Experiencing Scale. Analyses indicated a significantly higher number of high-arousal segment in the latter phase. Individual clients' change trajectories were not significantly steeper in the second phase. Experiencing increased throughout both phases of treatment. However, after introducing the two-chair dialogue the Experiencing change trajectory was not significantly steeper than in the baseline phase. Findings suggest that both the two-chair dialogue and the Rogerian conditions with affect attunement focus are effective in facilitating emotional processing. Results are consistent with previous research, suggesting that the two-chair dialogue is an emotionally evocative intervention. Implications and limitations are discussed.